Application of thermodynamic modeling to predict the stable hydrate phase assemblages in ternary CSA-OPC-anhydrite systems and quantitative verification by QXRD. (February 2020) - Wolf, J.J.; Jansen, D.; Goetz-Neunhoeffer, F.; Neubauer, J.
Abstract: Thermodynamic modeling was used to predict the stable hydrate phase assemblages in a ternary CSA-OPC-anhydrite system. On the basis of this modeling, five systems with diverging expected hydrate phases were chosen for experimental examination via QXRD and TGA. The aim of this study was to examine whether and to which extent the predicted equilibrium states are reached after 28 days of hydration. Qualitatively the predicted hydrate phase assemblages were reached for all five systems after 28 d of hydration. When the reaction degrees of the anhydrous phases are taken into account the experimental data fits remarkably well to the thermodynamic model. Additionally, C2 S dissolution was found to be the most rapid in straetlingite forming environments.